Bioactive Compounds and Microbacteria of Peel-Off Gel Mask Caulerpa racemosa - Putri, Tri Widayati; Karim, Mutemainna; Khairiyah, Zul; Ramadhani, Andi Fitri (Indonesian Journal of Chemical Research, 2023)
Caulerpa racemosa is a type of seaweed that has the potential to be cultivated because it is known and favored by the public.Caulerpa racemosa is used not only for consumption as food but also for beauty cosmetics because of its ingredients. This study aims to determine the Bioactive content and total plate count (TPC) of the Caulerpa racemosa peel-off gel mask. The pour plate method was used to determine the total plate number of mycobacteria and phytochemical testing in the form of tests for flavonoid, alkaloid, phenolic, tannin, triterpenoids, and saponin. The results showed that the total colony total plate count until the 3rd repetition had an average of 31 col/g. The results of the phytochemical test of the Caulerpa racemosa peel-off gel mask contained bioactive compounds: flavonoid, alkaloid, phenolic, tannins, triterpenoid, and saponin. Conclusion: The Total plate count of Caulerpa racemosa peel off the gel mask complies with Indonesian National standards (INS) with the content of bioactive compounds, namely tannins dan saponins. Caulerpa racemose was used for a pell-off gel mask for the first time.